Riscos potenciais do processo medicamentoso clínico em Unidade de Terapia Intensiva - Sidney, Kamila Maria Maranhão (2018)
Faced with the complexity of an Intensive Care Unit (ICU), the reality of a plurality of therapies, including pharmacological and advanced technologies, can render inpatient health care unsafe. The objective was to analyze potential risks of the clinical drug process in the Intensive Care Unit of a tertiary hospital in Ceará. The study is an action research, with a quantitative and qualitative approach of the observational type. Initially, the FMEA team was formed and after the analysis of the prescriptions released at the unit on Mondays, Wednesdays and Fridays between October 2017 and January 2018. The Microsoft Excel 2010® program was used to analyze the data and the Pareto principle to evaluate the occurrence of failure modes and the variance of these occurrences as well as the GUT matrix. For pharmaceutical interventions, a descriptive statistical analysis was performed. 170 prescriptions were analyzed, 63 possible potential failure modes were identified, among them: drug-drug or food-drug interaction (n = 25, 39.6%), incompatibilities (n = 18, 28.5%), and medications needed of renal adjustment (n = 9, 14.2%). It was found that for all drug-drug, drug-food and incompatibility interactions the causes were the same: lack of interaction / incompatibility by the medical and nursing staff. The severity indexes had a high score (n = 32; 53.3%) and moderate (n = 15; 25%) and a minimum score (n = 21; 35%). There were 39 (65%) failure modes and by Pareto analysis the most frequent occurrences were: lack of dosage form and dosage. In the Pareto analysis of CP, the following should be prioritized: absence of pharmaceutical form and Amiodarone + Atorvastatin. In the Pareto analysis of the GUT matrix, the ones with the highest criticality are: dose, Amiodarone + Amlodipine and Fentanyl + Amiodarone. There were 287 pharmaceutical interventions (IFs), in which 70.03% (n = 201) were accepted, contact was made with medical staff in 93.38% (n = 268). Improvement actions were also carried out involving the continued education of the multiprofessional team. The study allowed to identify and analyze the modes and effects of the failures identified in the clinical drug process, besides revealing the necessity of the elaboration of protocols and standardization of processes involving the use of medications.